Perumusan Strategi Operasi-Produksi Kosmetik (Studi Kasus PT ANI) - Dwiyanti, Rizda; Hubeis, Musa; Suprayitno, Gendut (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
Policy ASEAN Economic Community (AEC) lead to competition in the cosmetics industry is increasing. Performance operation-production must be increased in order to produces cosmetic quality standards of ASEAN. Research conducted in medium-scale cosmetic companies PT ANI, with the aim of determining the mission and objectives, business strategy, operating strategy based on priority performance goals operation-production function and formulate strategy and policy for operation-production resource and process development. Research methods with descriptive qualitative and and analysis tools used are SWOT analysis, SFAS matrix, Porter Generic Strategy, TOWS matrix,   operations strategy matrix and the AHP for weighting internal/eksternal strategic factors and prioritize operation-production strategy determination. Based on the results of this study concluded that PT ANI mission is produce facial and personal care cosmetics using natural active ingredients that are safe and good quality, to capture domestic and overseas niece market. The company's business strategy is competitive strategy of differentiation focus and serve the manufacture of face and personal care cosmetics with variants and volume according to customer requirements.  The development of resources and operation-production  processes priority is to meet the five performance objectives, namely quality (0,454), reliability (0,270), flexibility (0,147), speed (0,082) and cost (0,048). On the other hand operation-production strategic priority to meet the performance targets is a process technology (0,425), supply chain network (0,235), capacity (0,206), the development and organization (0,133).